Outcomes after intensive care unit admission in newly diagnosed diffuse large B‐cell lymphoma patients: A real‐life study. (5th March 2021) - Zduniak, Alexandra; Mihailescu, Sorina‐Dana; Lequesne, Justine; Lenain, Pascal; Contentin, Nathalie; Pepin, Louis‐Ferdinand; Ménard, Anne‐Lise; Leprêtre, Stéphane; Lemasle, Emilie; Lanic, Hélène; Stamatoullas‐Bastard, Aspasia; Tilly, Hervé; et al.
Abstract: We conducted a retrospective study to analyze the prognostic factors impacting the overall survival (OS) and progression‐free survival (PFS) of diffuse large B‐cell lymphoma (DLBCL) patients undergoing first‐line therapy and admitted to intensive care unit (ICU) compared to a control cohort who did not required ICU admission. Between January 1, 2008, and December 31, 2018, 828 patients were diagnosed with DLBCL at our institution, including 72 patients who were required ICU admission during disease course. Among them, forty‐five patients undergoing homogeneous first‐line therapy with /R‐CHOP‐like regimen and ICU‐admitted were selected for the present analysis. Control "non‐ICU" DLBCL patients were matched by age, IPI score and treatment received. The median age at ICU admission was 65 years, 97.8% of patients displayed advanced‐stage disease (III/IV), and 84.4% had a high IPI score (3‐5). The main reasons for ICU admission were acute respiratory failure (40.0%) and septic shock (33.3%). The ICU mortality rate was 33.3%. The 2‐year PFS was lower in ICU survivors patients than in non‐ICU patients: 31.7% (95% CI 18.5‐54.1) vs 60.8% (95% CI 51.2‐72.1, P = .00049). Admission to the ICU is an event that clearly impacts the outcomes of patients with DLBCL, until 2 years after the event. ICU prognosis seems mainly related to critical patient severity at admission rather than lymphoma‐related prognostic factors (IPIs), suggesting that ICU admission criteria should not be based only on the lymphoma prognosis.